When the Pentagon Was for Sale : Inside America's Biggest Defense Scandal - Pastor, Andy (New York Scribner, 1995)
The definitive expos of the reprehensible criminals who "wrapped themselves in the American flag just to line their own pockets" when Ronald Reagan was president and the United States was spending more than $30 million an hour, twenty-four hours a day, seven days a week, on defense.
Include Index, Notes and Epilogue.
This troubling tale starts with "two scared little girls, the frightfully troubled man who accosted them and the tiny puddle of semen on the grimy basement floor" and spreads to "the biggest Pentagon corruption scandal in history." Pasztor's expose describes Operation Illwind, the investigation and prosecution of a score of officials and contractors who indulged in fraudulent acquisition practices. Big money from lucrative weapons contracts was illegally gained through insider knowledge and pernicious document swapping that "compromised the integrity of the military's procurement system." Basing his book on over 130 interviews (with FBI agents, industrialists, senators, and Defense and Navy secretaries) and a meticulous review of trial transcripts and wiretaps, Pasztor, a Wall Street Journal reporter, doesn't need the innuendos and insinuations that he succumbs to at times. For popular collections.
Keywords: United States. -- United States -- Politics and Government -- 1981-1989.